2021
DOI: 10.3390/app112210618
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Determinants for Adoption of Intelligent Personal Assistant: An Empirical Study

Abstract: With the accelerating advances in artificial intelligence (AI) technologies, the rising demand for the intelligent personal assistant is expected to rapidly increase in the following decades. As customer loyalty has become a critical element in gaining a competitive advantage and many marketers pay great attention to it, this research aims to explore the factors that directly affect customer loyalty toward the intelligent personal assistant. The main motivation is to investigate and identify the direct effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…The term of perceived value, initially introduced by Dodds and Monroe [84], centers around the balance between how customers perceive quality or benefits and what they are willing to pay or sacrifice. Perceived value involves assessing the overall usefulness by comparing the benefits gained with the sacrifices incurred [85,86]. A study in a journal focused on the adoption of intelligent personal assistants discovered that customers' readiness to use the product is notably affected by their perception of functional, social, and knowledge-related values [86].…”
Section: Perceived Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…The term of perceived value, initially introduced by Dodds and Monroe [84], centers around the balance between how customers perceive quality or benefits and what they are willing to pay or sacrifice. Perceived value involves assessing the overall usefulness by comparing the benefits gained with the sacrifices incurred [85,86]. A study in a journal focused on the adoption of intelligent personal assistants discovered that customers' readiness to use the product is notably affected by their perception of functional, social, and knowledge-related values [86].…”
Section: Perceived Valuesmentioning
confidence: 99%
“…Perceived value involves assessing the overall usefulness by comparing the benefits gained with the sacrifices incurred [85,86]. A study in a journal focused on the adoption of intelligent personal assistants discovered that customers' readiness to use the product is notably affected by their perception of functional, social, and knowledge-related values [86]. Furthermore, additional research studies identified that the perception of value has a direct impact on the willingness to embrace various forms of information technology, for instance, the acceptance of mobile payment solutions [69] and adoption of assistance products such as smart speaker, voice assistance, home appliances [87].…”
Section: Perceived Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial Intelligence functions as merely a technology to perform everyday life functions. People preferring smartphones having AI-based voice assistance have concerns regarding the self-efficacy and problem-solving of the assistant [53].…”
Section: The Role Of Satisfaction and Attitude In Intention To Use Sirimentioning
confidence: 99%
“…Besides these technical developments, researchers are emphasizing the need for research in COVID19-induced brain dysfunction (CIBD) to improve the mental health of large populations of infected/uninfected individuals [288]. Despite these highlighted areas and developments, AI's role in COVID-19 and post COVID-19 era can offer a proven method to further strengthen the impact of healthcare services/applications on population health, which is more necessary than ever in the post-COVID era [289][290][291][292]. To this end, further developments are needed to lower the effects of this pandemic and to serve mankind effectively in these unanticipated and challenging times.…”
Section: Future Research Directionsmentioning
confidence: 99%